Rice water requirement exacerbates groundwater depletion in Northeast China under a changing climate - Zhao, Yuanbo; Li, Tao; Zhao, Jin; Zhang, Zhentao; Liu, Runze; Shi, Yanying; Ma, Haoyu; Zhao, Chuang; Liu, Zhijuan; Yang, Xiaoguang (Elsevier, 2025)
In recent years, Northeast China (NEC) has emerged as a key rice production region. However, the region’s scarce precipitation and surface water availability raise concerns about groundwater over intensive rice cultivation. Using the process-based rice model ORYZA (v3), we assessed irrigation water demand and groundwater depletion under two irrigation regimes - Flood (FLD) Irrigation and Alternative Wet-dry (AWD) Irrigation - across two climate change scenarios (SSP1–2.6 and SSP5–8.5). Results indicated a substantial increase in irrigation water demand (28.6 % to 52.3 %) and groundwater depletion ratio (23.6 % to 53.0 %) under future climate scenarios, with higher impacts under the more extreme SSP5–8.5 pathway. Spatial analysis revealed that regions with larger rice cultivation areas, particularly in Sanjiang Plain, are more vulnerable to groundwater depletion. Furthermore, the benefits of AWD irrigation in mitigating water stress decline under climate change, with reductions in groundwater extraction alleviation (by 7.6 % to 7.9 %) and water use efficiency improvement (by 8.1 % to 8.3 %). These findings underscore the urgent need for spatially optimized rice cultivation and adaptive irrigation strategies tailored to ensure long-term groundwater sustainability and regional food security.